Reconstruction of Nasal Alar Defects with Freestyle Facial Artery Perforator Flaps - D'Arpa, Salvatore; Pirrello, Roberto; Toia, Francesca; Moschella, Francesco; Cordova, Adriana (Facial Plastic Surgery, 2014)
In 2009, we have described the use of freestyle facial artery perforator flaps for one-stage nose reconstruction. Since then, several articles have reported the use of facial artery perforator flaps for nose reconstruction. The purpose of this article is to provide an update of the published technique after 10 years of experience. Since 2004, 21 patients have been treated with a freestyle facial artery perforator flap for one-stage reconstruction of the nasal ala. The flaps were 16 propellers, 4 V-Y, and 1 island transposition. A single venous congestion leading to a minor flap tip necrosis and a wound dehiscence was observed. All other flaps healed uneventfully. The V-Y design and multiple subunit reconstruction gave suboptimal results. It was concluded that indications for freestyle facial artery perforator flaps are total nasal alar subunit reconstruction or reconstruction of lateral alar defects when perforator anatomy allows. In these cases, freestyle facial artery perforator flaps are the first choice technique at our institution because they allow excellent results in one-stage operation. One-stage nasal ala reconstruction with freestyle facial artery perforator flaps.
Keywords: freestyle flap; propeller flap; perforator flap; facial artery perforator; nose; reconstruction